2017
DOI: 10.1039/c7cp01526g
|View full text |Cite
|
Sign up to set email alerts
|

Diacetylene polymerization on a bulk insulator surface

Abstract: Molecular electronics has great potential to surpass known limitations in conventional silicon-based technologies. The development of molecular electronics devices requires reliable strategies for connecting functional molecules by wire-like structures. To this end, diacetylene polymerization has been discussed as a very promising approach for contacting single molecules with a conductive polymer chain. A major challenge for future device fabrication is transferring this method to bulk insulator surfaces, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 35 publications
(38 reference statements)
1
37
0
Order By: Relevance
“…35,36 Furthermore, it was shown that for electronic devices with predominant lateral transport the spacer layers must have a thickness of at least 3-4 monolayers (ML) 35 and when permanent charging of single molecules is desired, the layer must be even thicker. 39 On bulk insulating substrates, successful polymerization was so far obtained on calcite 40,41,42,43,44 and mica 45 surfaces which have a high surface energy 46 and provide a strong anchoring of the molecules to the substrates which allows for relatively large annealing temperatures (500K). 42 UV-induced polymerization on bulk insulators was demonstrated for pre-arranged supramolecular structures for both 1D 44 and 2D structures.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36 Furthermore, it was shown that for electronic devices with predominant lateral transport the spacer layers must have a thickness of at least 3-4 monolayers (ML) 35 and when permanent charging of single molecules is desired, the layer must be even thicker. 39 On bulk insulating substrates, successful polymerization was so far obtained on calcite 40,41,42,43,44 and mica 45 surfaces which have a high surface energy 46 and provide a strong anchoring of the molecules to the substrates which allows for relatively large annealing temperatures (500K). 42 UV-induced polymerization on bulk insulators was demonstrated for pre-arranged supramolecular structures for both 1D 44 and 2D structures.…”
Section: Main Textmentioning
confidence: 99%
“…39 On bulk insulating substrates, successful polymerization was so far obtained on calcite 40,41,42,43,44 and mica 45 surfaces which have a high surface energy 46 and provide a strong anchoring of the molecules to the substrates which allows for relatively large annealing temperatures (500K). 42 UV-induced polymerization on bulk insulators was demonstrated for pre-arranged supramolecular structures for both 1D 44 and 2D structures. 42 (ii) The so far largest, defect-free organic layers have been achieved by supramolecular selfassembly (SA) in which the molecule-molecule (MM) interaction is dominated by relatively weak and reversible Van der Waals (VdW) or Hydrogen bonding.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the molecule is also equipped with two carboxylic acid functionalities, which have previously proven to act as suitable anchors on the calcite (10.4) surface and prevent the desorption at elevated temperatures. Density-functional theory calculations have suggested an interaction of the carbonyl groups with the calcium ions via electrostatics, while the hydroxyl groups form hydrogen bonds with the calcite carbonate group oxygen atoms [23,24] . Furthermore, a detailed investigation towards a possible deprotonation has been performed, suggesting a transition of the hydrogen from the hydroxyl group towards the oxygen of the carbonate group under formation of a hydrogen bond [23,24] .…”
Section: Introductionmentioning
confidence: 99%
“…Density-functional theory calculations have suggested an interaction of the carbonyl groups with the calcium ions via electrostatics, while the hydroxyl groups form hydrogen bonds with the calcite carbonate group oxygen atoms [23,24] . Furthermore, a detailed investigation towards a possible deprotonation has been performed, suggesting a transition of the hydrogen from the hydroxyl group towards the oxygen of the carbonate group under formation of a hydrogen bond [23,24] . Two anchor groups were chosen here for symmetry reasons and to also promote molecule-molecule interactions that can be beneficial for the formation of an ordered selfassembled structure as compared to mobile species.…”
Section: Introductionmentioning
confidence: 99%